Engelskpåvirkningen af dansk skriftsprog: Nogle hovedresultater fra projektet Yes, det er coolt. Om påvirkning af dansk fra andre sprog - Andersen, Margrethe Heidemann (Studier i Nordisk, 2022)
In this article I describe some of the results of the project ”Yes, det er coolt. Om påvirkning af dansk fra andre sprog” (“Yes, it’s coolt. On foreign influence on the Danish language”). The project is a continuation of a Nordic research project in which the use of words from foreign languages (mainly English) in Nordic newspapers from 1975 and 2000 was described. One of the most important results from the new research project was that even though we still mainly borrow words from the English language, the amount of English words in Danish has not increased in the period from 2000 till 2016. Another important result is that we borrow more verbs from English than before, e.g. verbs as facebooke, hacke and maile (with a Danish inflectional e) which are associated with the internet and to the social media.